UNDERSTANDING THE INTENTION OF MILLENNIAL GENERATION ON INVESTMENT THROUGH THE FINANCIAL TECHNOLOGY APPLICATION - Chalimatuz Sa'diyah; Yeyen Pratika (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The financial technology (fintech) companies utilize social media for many purposes. The increasing of digitalization in the fintech companies make consumers easier to make a purchase or an investment. This condition provides a phenomenon in which young generation is willing to invest their funds through fintech system. The purpose of this study is to examine whether social media marketing influences the intention of the young generation in investing. A total of 208 respondents coming from millennial generation involved in this study. Structural Equation Modeling (SEM) was used to analyze this research with the results showing that perceived relevance, informativeness, and utilitarian motivation have significant effect on millennial generation's intention to invest. In addition, perceived relevance and informativeness also influence utilitarian motivation.